Links to rare climates do not translate into distinct traits for island endemics. (5th February 2023) - Cutts, Vanessa; Hanz, Dagmar M.; Barajas‐Barbosa, Martha Paola; Schrodt, Franziska; Steinbauer, Manuel J.; Beierkuhnlein, Carl; Denelle, Pierre; Fernández‐Palacios, José María; Gaüzère, Pierre; Grenié, Matthias; Irl, Severin D. H.; Kraft, Nathan; et al.
Abstract: Current models of island biogeography treat endemic and non‐endemic species as if they were functionally equivalent, focussing primarily on species richness. Thus, the functional composition of island biotas in relation to island biogeographical variables remains largely unknown. Using plant trait data (plant height, leaf area and flower length) for 895 native species in the Canary Islands, we related functional trait distinctiveness and climate rarity for endemic and non‐endemic species and island ages. Endemics showed a link to climatically rare conditions that is consistent with island geological change through time. However, functional trait distinctiveness did not differ between endemics and non‐endemics and remained constant with island age. Thus, there is no obvious link between trait distinctiveness and occupancy of rare climates, at least for the traits measured here, suggesting that treating endemic and non‐endemic species as functionally equivalent in island biogeography is not fundamentally wrong. Abstract : Current models of island biogeography treat endemic and non‐endemic species as if they were functionally equivalent. Incorporating plant functional trait data into island theory, we find no obvious link between trait distinctiveness and occupancy of rare climates, suggesting that treating endemic and non‐endemic species as functionally equivalent in island biogeography is not fundamentally wrong.